2022
DOI: 10.1101/2022.11.11.22282206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topological changes of fast large-scale brain dynamics in Mild Cognitive Impairment predict the decay of the hippocampal memory

Abstract: Functional connectivity has been widely used as a framework to investigate widespread brain interactions underlying cognitive deficits in Mild Cognitive Impairment (MCI). However, one of the main constraints of functional connectivity is that it is averaged over a time interval and therefore may not take into account the aperiodic and scale-free burst of activity (i.e., the neuronal avalanches) characterising the large-scale dynamic activity of the brain. Here, we used the recently proposed Avalanche Transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“… 17 Indeed, a number of theoretical and numerical results show that criticality is associated with optimal information processing and computation. 17 , 18 , 19 , 20 Moreover, reduced flexibility 21 , 22 , 23 , 24 and breakdown (or alteration) of long-range temporal correlations in brain dynamics 25 , 26 have been associated with neurological diseases and reduced information transfer.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Indeed, a number of theoretical and numerical results show that criticality is associated with optimal information processing and computation. 17 , 18 , 19 , 20 Moreover, reduced flexibility 21 , 22 , 23 , 24 and breakdown (or alteration) of long-range temporal correlations in brain dynamics 25 , 26 have been associated with neurological diseases and reduced information transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigated the flexibility of the brain dynamics in MS and its relationship with the clinical phenotypes. In particular, following our previous studies carried out on neurodegenerative diseases, including ALS 18 , AD 19 and PD 17 , where a reduction of the functional repertoire has been consistently found, we hypothesised that MS could express different behaviours as a function of the prevalence of neuroinflammation or neurodegeneration. When we looked at the different MS clinical phenotypes, we found that the significant differences in the flexibility of the brain dynamics were mainly attributable to the RRMS phenotype.…”
Section: Discussionmentioning
confidence: 93%
“…Based on our previous observations about brain dynamics in neurodegenerative diseases such as probable Alzheimer's disease (AD) 19 , Parkinson's disease (PD) 17 and Amyotrophic lateral sclerosis (ALS) 18 , in the present work we hypothesise that MS could also be characterised by variations in brain flexibility, which would be related to, and predictive of, the subject specific clinical impairment. We also wondered whether the underlying disease mechanisms that characterise the two distinct forms of MS (relapsing remitting and progressive) could reflect in different brain dynamics and if this difference could help in predicting clinical disability.…”
Section: Introductionmentioning
confidence: 81%